If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -40 + -2k = -6(6 + k) -40 + -2k = (6 * -6 + k * -6) -40 + -2k = (-36 + -6k) Solving -40 + -2k = -36 + -6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '6k' to each side of the equation. -40 + -2k + 6k = -36 + -6k + 6k Combine like terms: -2k + 6k = 4k -40 + 4k = -36 + -6k + 6k Combine like terms: -6k + 6k = 0 -40 + 4k = -36 + 0 -40 + 4k = -36 Add '40' to each side of the equation. -40 + 40 + 4k = -36 + 40 Combine like terms: -40 + 40 = 0 0 + 4k = -36 + 40 4k = -36 + 40 Combine like terms: -36 + 40 = 4 4k = 4 Divide each side by '4'. k = 1 Simplifying k = 1
| 5/8-1/2=3/4y | | 4*y=14y+4*3 | | 2x-y=1000 | | 3x+4x+6x=39 | | -t^2+31t-145=0 | | 2m/5=1/3(2m-12 | | -9=-6(-1+4n)-1 | | ax=y-7 | | x/8=.48 | | 10k-(2k-6)-(2k-3)=-4 | | 4x+3(2x+7)=81 | | -2x+10=-24 | | 2k+3(2k+2)=2(3k-1) | | 0=/9 | | 121=5+6(-4v+5) | | 8c-4=20 | | n=5-2+4 | | 8w+2x-6w+3w= | | -2(q-29)=-1/2(4-8q) | | 4y-12x=108 | | T+19=25 | | 4x-2(x-3)=-7+5x-8 | | -9x+-3=24 | | 7(n+7)=19+2n | | .3*300=x | | 0.03=6 | | 18(x-1)=12(x+3) | | 8x+10x=7 | | .3*300= | | 6(a+4)(a-7)=0 | | 7st+6su+8sv= | | X-6=7y |